Spinal osteotomies: indications, limits and pitfalls - İĞREK, SERVET (BRITISH EDITORIAL SOC BONE & JOINT SURGERY, 2017)
The aims of spinal deformity surgery are to achieve balance, relieve pain and prevent recurrence or worsening of the deformity. The main types of osteotomies are the Smith-Petersen osteotomy (SPO), pedicle subtraction osteotomy (PSO), bone-disc-bone osteotomy (BDBO) and vertebral column resection (VCR), in order of increasing complexity. SPO is a posterior column osteotomy in which the posterior ligaments and the facet joints are removed and correction is performed through the disc space. A mobile anterior disc is essential. SPO is best in patients with + 6-8 cm C7 plumbline. The amount of correction is 9.3 degrees to 10.7 degrees/level (1 degrees/mm bone). PSO is a technique where the posterior elements and pedicles are removed. Then a triangular wedge through the pedicles is removed and the posterior spine is shortened using the anterior cortex as a hinge. The ideal candidates are patients with a severe sagittal imbalance. A single level osteotomy can produce 30 degrees 40 degrees of correction. A single level osteotomy may restore global sagittal balance by an average of 9 cm with an upper limit of 19 cm. BDBO is an osteotomy done above and below a disc level. A BDBO provides correction rates in the range of 35 degrees to 60 degrees. The main indications are deformities with the disc space as the apex and severe sagittal plane deformities. VCR is indicated for rigid multi-planar deformities, sharp angulated deformities, hemivertebra resections, resectable spinal tumours, post-traumatic deformities and spon-dyloptosis. The main indication for a VCR is fixed coronal plane deformity. The type of osteotomy must be chosen mainly according to the aetiology, type and apex of the deformity. One may start with SPOs and may gradually advance to complex osteotomies.
Keywords: VERTEBRAL COLUMN RESECTION; PEDICLE SUBTRACTION OSTEOTOMY; FIXED SAGITTAL IMBALANCE; POSTERIOR SURGERY; PLANE DEFORMITY; SMITH-PETERSEN; SCOLIOSIS; MANAGEMENT; DECOMPENSATION; KYPHOSIS